ANALISIS PENGARUH SIKAP PERCAYA DIRI SISWA DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PBL BERBANTUAN BAHAN MANIPULATIF - Maria Trisna Sero Wondo; Konstantinus Denny Pareira Meke (Program Studi Pendidikan Matematika, 2021)
This study aims to analyze self-confidence using the PBL model assisted by manipulatif materials. Sample in this study were students of class VIII SMPK Maria Goretti Ende in the 2019/2020 school year totaling 30 people. This research uses survey and correlational methods. The research instrument was a non-test instrument, namely a questionnaire composed of 20 items based on indicators of self-confidence, namely: 1) self-confidence, 2) assertiveness, 3) responsibility, 4) positive thinking. The results showed that learning mathematics using the PBL model assisted by manipulatif materials in class VIII students of SMPK Maria Goretti Ende in the 2019/2020 school year received a positive response where the average student had a high self-confidence indicator of 65.1%.